Association between maternal death and cesarean section in Latin America: A systematic literature review. (April 2018) - Fahmy, Walid Makin; Crispim, Cibele Aparecida; Cliffe, Susan
Abstract: Background: it is critically important to explore a possible relationship between cesarean section and maternal mortality in Latin America, where the highest cesarean section rates in the world are found. Our aim was to conduct a systematic literature review on the relationship between maternal death and caesarean section in Latin America. Methods: we undertook a systematic review through six electronic databases. Studies that reported any association analysis between maternal mortality and the mode of delivery in Latin America were included. Papers that fulfilled the inclusion criteria were then read fully, and a quality assessment was conducted with the PROMPT tool. Results: seven articles were identified for final analysis, all of which were observational studies. Most of the studies were retrospective (6) and one was prospective. Of the retrospective studies, 3 were case control and 3 were cross-sectional. Most of the publications on this topic suggest that there may be an increased risk of maternal mortality with cesarean section compared with vaginal birth (odds ratio ranging from 1.6 to 7.08). However, it is evident that there is a lack of studies with this subject, especially those that take into account the differences in risk between women delivered by cesarean section or by vaginal birth. Conclusions: most of the articles showed that there may be an increased risk of maternal mortality with cesarean section compared with vaginal birth. However, it is clear that there is a limited number of studies published on this issue. Additional studies with a better methodological design should be conducted. Highlights: A systematic review through six electronic databases was conducted. Seven articles were identified for final analysis. There might be a greater risk of maternal death with cesarean section than with vaginal birth.